Pulmonary Complication in Bone Marrow Transplant Patients - Sobidar Khan; Shamimah Hanif; Sarfraz Ahmad; Muhammad Ishaque; Fazal Ur Rehman; Saeed Khan; Syed Sadiq Ullah; Syed Nadir Shah; Saidal Durrani (Indus Journal of Bioscience Research, 2025)
Background: Patients receiving bone marrow transplantation (BMT) frequently experience pulmonary problems, which are a major cause of morbidity and death. These issues arise at different points during the post-transplant phase and might be either infectious or noninfectious. Objective: The purpose of this study is to investigate the prevalence, kinds, methods of diagnosis, and consequences of pulmonary problems in BMT patients at a Quetta tertiary care facility. Methods: A Quetta tertiary care hospital served as the site of this qualitative investigation. One hundred and twenty post-BMT patients were chosen as a purposive sample. Semi-structured interviews with patients and healthcare professionals as well as examinations of clinical records were used to gather data. Classifying pulmonary problems and determining related risk variables were the main objectives of the analysis. Results: 78.3% of the 120 BMT patients experienced pulmonary problems, of which 26.7% were noninfectious and 52% were infectious (28.3% fungal). Mortality was 21%; 23.3% required intensive care unit care. The diagnostic yield for bronchoscopy was 70%. After transplantation, 55.8% of patients experienced ongoing respiratory problems. Conclusion: Patients who have bone marrow transplants continue to face pulmonary problems, which have a substantial influence on morbidity and death. For post-transplant recovery to be more successful and to increase quality of life, early diagnosis, preventive measures, and customized treatment are crucial.